Hemispheric asymmetries in the processing of body sides: A study with ambiguous human silhouettes. (24th August 2017) - Marzoli, Daniele; Pagliara, Alessandra; Prete, Giulia; Malatesta, Gianluca; Lucafò, Chiara; Padulo, Caterina; Brancucci, Alfredo; Tommasi, Luca
Highlights: Both hemispheres notoriously show a processing advantage for contralateral body parts. We tested whether a similar effect is found with ambiguous human silhouettes. Stimuli were perceived as right-handed more often when presented to the right visual field. Each hemisphere is biased to perceive contralateral hand actions in ambiguous human bodies. Abstract: When required to indicate the perceived orientation of pictures of human silhouettes with ambiguous front/back orientation and handedness, both right- and left-handed participants perceive the figures more frequently as right-handed than as left-handed, which seems to indicate an attentional bias towards the right arm of human bodies. Given that past research exploiting the divided visual field paradigm indicated a processing advantage for contralateral body parts in both hemispheres, we tested whether human silhouettes with ambiguous handedness presented in the right visual field would be interpreted more frequently as right-handed compared with those presented in the left visual field. We confirmed the expected lateralised embodiment of ambiguous human bodies, in line with previous studies showing that right and left limbs are processed faster and/or more accurately when presented in the right and left hemifield, respectively.